THE ISLAMIC QUALITY MANAGEMENT SYSTEM IN MALAYSIA: A NARRATIVE REVIEW - Fadzila Azni Ahmad; Mohd Sadiq Mohd Mokhtar (Journal of Islamic, Social, Economics and Development, 2019)
Since the industrial revolution started, the quality management system has been a major focus area to many nations including developing nation such as Malaysia. The quality management system has been implemented in many sectors in the world to accommodate the demand for quality products and services. The quality management system has been focussing on the aspects of achieving the quality demand and reducing the production cost which eventually benefits the institution in terms of material aspects. Meanwhile, Islamic Quality Management System has been developed and getting attention in Muslim majority countries such as Malaysia. As an Islamic country, Malaysia has taken a step forward by formulating MS1900 which known as quality management system requirements from Islamic perspectives. Therefore, this has shown the interest of Malaysia in focussing on Islamic quality management system. In line with this, questions arise about the relevance of Islamic Quality Management System in Malaysia. Thus, this paper aims to evaluate the Islamic Quality Management System in Malaysia based on the researcher perspectives by narrative review approach. The narrative reviews approach was employed in undertaking the literature search for selected articles based on the inclusion and exclusion criteria. The focus of narrative reviews is to identify common themes across research regarding Islamic Quality Management System in Malaysia that then can be used to identify commonalities and critical differences among included documents. The paper utilises interpretive inquiry of the texts mainly from the related literature in the research area. The findings reveal that Islamic Quality Management System in Malaysia was a great step towards developing a quality management system that compromise of spiritual aspect and benefitted Muslim in this world and Hereafter. There are benefits, special characteristic, principles and issue found regarding Islamic Quality Management System in this research